RITUS HODE ILU DALAM MASYARAKAT LEWOINGU: ANTARA TINDAKAN SUPERSTISI DAN REALITAS NUMINUS - Bernard Subang Hayong (Jurnal Ledalero, 2011)
The human propensity of openness to the transcendent can be seen as a fundamental predisposition. It is also a need. We encounter such a need in numerous traditions and cultures, including in postmodern societies. In the Hode Ilu ritual, the people of the Lewoingu domain of Eastern Flores (Kabupaten Flores Timur, NTT), express the inseparableness of cosmic reality (humans and their world) with transcendent reality. They experience nature as numinus with supernatural power. This power enables people to submit in awe and act out the heritage of the ancestors in an artistic performance expressing people’s relationship with others, nature, oneself, and with the Divine. This ritual performance is called “artistic” because it is a self expression of the community through ritual that emphasises a fundamental cosmic harmony which is both religious (transcendent) and ethical (in the here and now). When the tradition expresses a form of faith in the transcendent in ritual, then the sharing of human experiences, including relationships of people with the Transcendent, with the cosmos, with others, and with oneself, is not wrong. Also, in such ritual performances, we see a change of perspective and a change in human action regarding oneself, others, nature (with its powers), and with the Divine.